Comparative study of thermally activated delayed fluorescent properties of donor–acceptor and donor–acceptor–donor architectures based on phenoxazine and dibenzo[a,j]phenazine - Izumi, Saika; Govindharaj, Prasannamani; Drewniak, Anna; Crocomo, Paola Zimmermann; Minakata, Satoshi; de Sousa, Leonardo Evaristo; de Silva, Piotr; Data, Przemyslaw; Takeda, Youhei (Beilstein Journal of Organic Chemistry, 2022)
A new thermally activated delayed fluorescence (TADF) compound based on a donor–acceptor (D–A) architecture (D = phenoxazine; A = dibenzo[a,j]phenazine) has been developed, and its photophysical properties were characterized. The D–A compound is applicable as an emitting material for efficient organic light-emitting diodes (OLEDs), and its external quantum efficiency (EQE) exceeds the theoretical maximum of those with prompt fluorescent emitters. Most importantly, comparative study of the D–A molecule and its D–A–D counterpart from the viewpoints of the experiments and theoretical calculations revealed the effect of the number of the electron donor on the thermally activated delayed fluorescent behavior.
Keywords: charge-transfer; dibenzophenazine; donor–acceptor; organic light-emitting diodes; thermally activated delayed fluorescence

(untitled) - Parker, C. A.; Hatchard, C. G. (Trans. Faraday Soc., 1961)

(untitled) - Uoyama, H.; Goushi, K.; Shizu, K.; Nomura, H.; Adachi, C. (Nature, 2012)

(untitled) - Tao, Y.; Yuan, K.; Chen, T.; Xu, P.; Li, H.; Chen, R.; Zheng, C.; Zhang, L.; Huang, W. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Yang, Z.; Mao, Z.; Xie, Z.; Zhang, Y.; Liu, S.; Zhao, J.; Xu, J.; Chi, Z.; Aldred, M. P. (Chem. Soc. Rev., 2017)

(untitled) - Liu, Y.; Li, C.; Ren, Z.; Yan, S.; Bryce, M. R. (Nat. Rev. Mater., 2018)

(untitled) - Huang, T.; Jiang, W.; Duan, L. (J. Mater. Chem. C, 2018)

(untitled) - Chen, X.-K.; Kim, D.; Brédas, J.-L. (Acc. Chem. Res., 2018)

(untitled) - Nakanotani, H.; Tsuchiya, Y.; Adachi, C. (Chem. Lett., 2021)

(untitled) - Nguyen, V.-N.; Kumar, A.; Lee, M. H.; Yoon, J. (Coord. Chem. Rev., 2020)

(untitled) - Candish, L.; Collins, K. D.; Cook, G. C.; Douglas, J. J.; Gómez-Suárez, A.; Jolit, A.; Keess, S. (Chem. Rev., 2022)

(untitled) - Data, P.; Takeda, Y. (Chem. – Asian J., 2019)

(untitled) - de Silva, P. (J. Phys. Chem. Lett., 2019)

(untitled) - Wagner, J.; Zimmermann Crocomo, P.; Kochman, M. A.; Kubas, A.; Data, P.; Lindner, M. (Angew. Chem., Int. Ed., 2022)

(untitled) - Im, Y.; Kim, M.; Cho, Y. J.; Seo, J.-A.; Yook, K. S.; Lee, J. Y. (Chem. Mater., 2017)

(untitled) - de Silva, P.; Kim, C. A.; Zhu, T.; Van Voorhis, T. (Chem. Mater., 2019)

(untitled) - de Sousa, L. E.; de Silva, P. (ChemRxiv, 2022)

(untitled) - Data, P.; Pander, P.; Okazaki, M.; Takeda, Y.; Minakata, S.; Monkman, A. P. (Angew. Chem., Int. Ed., 2016)

(untitled) - Izumi, S.; Higginbotham, H. F.; Nyga, A.; Stachelek, P.; Tohnai, N.; de Silva, P.; Data, P.; Takeda, Y.; Minakata, S. (J. Am. Chem. Soc., 2020)

(untitled) - Dias, F. B.; Penfold, T. J.; Monkman, A. P. (Methods Appl. Fluoresc., 2017)

(untitled) - Stein, T.; Kronik, L.; Baer, R. (J. Am. Chem. Soc., 2009)

(untitled) - de Sousa, L. E.; de Silva, P. (J. Chem. Theory Comput., 2021)

NEMO, Version 0.2.0 (de Sousa, L. E.)

(untitled) - Shao, Y.; Gan, Z.; Epifanovsky, E.; Gilbert, A. T. B.; Wormit, M.; Kussmann, J.; Lange, A. W.; Behn, A.; Deng, J.; Feng, X.; Ghosh, D.; Goldey, M.; et al. (Mol. Phys., 2015)